The first-in-human study of the pan-PIM kinase inhibitor PIM447 in patients with relapsed and/or refractory multiple myeloma - Raab, Marc-Steffen; Thomas, Sheeba K.; Ocio, Enrique M.; Guenther, Andreas; Goh, Yeow-Tee; Talpaz, Moshe; Hohmann, Nicolas; Zhao, Sylvia; Xiang, Fang; Simon, Carl; Vanasse, K. Gary; Kumar, Shaji K. (Leukemia, 2019)
PIM447, a novel pan-PIM inhibitor, has shown preclinical activity in multiple myeloma (MM). In the multicenter, open-label, first-in-human study, patients with relapsed and/or refractory MM were enrolled to determine the maximum-tolerated dose (MTD) or recommended dose (RD), safety, pharmacokinetics, and preliminary anti-myeloma activity of PIM447. PIM447 was administered in escalating oral doses of 70-700 mg once daily (q.d.) for 28-day continuous cycles. Seventy-nine patients with a median of four prior therapies were enrolled. Seventy-seven patients (97.5%) had an adverse event (AE) suspected as treatment related, with treatment-related grade 3/4 AEs being mostly hematologic. Eleven dose-limiting toxicities occurred, and an MTD of 500 mg q.d. and an RD of 300 mg q.d. were established. The main reason for discontinuation was disease progression in 54 patients (68.4%). In the entire study population, a disease control rate of 72.2%, a clinical benefit rate of 25.3%, and an overall response rate of 8.9% were observed per modified International Myeloma Working Group criteria. Median progression-free survival at the RD was 10.9 months. PIM447 was well tolerated and demonstrated single-agent antitumor activity in relapsed/refractory MM patients, providing proof of principle for Pim (Proviral Insertions of Moloney Murine leukemia virus) kinase inhibition as a novel therapeutic approach in MM.